2020
DOI: 10.1136/bmjopen-2019-034542
|View full text |Cite
|
Sign up to set email alerts
|

The extent to which family physicians record their patients’ exercise in medical records: a scoping review

Abstract: ObjectiveExercise is an effective modality for the prevention and treatment of chronic conditions and family physicians are the healthcare providers tasked to manage patients’ chronic disease status. However, little is known about the exercise documentation in family-physician records. Therefore, a scoping review was conducted to describe family-physician-recorded exercise-related advice to patients in electronic medical records.DesignScoping review.SettingPrimary care clinics.Search strategyPubMed, Medline, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Despite a rise in initiatives and research, 61 physical activity promotion in primary care remains inconsistent. [62][63][64][65][66][67] Exercise referral schemes have shown small positive effects on physical activity, 33 but with low attendance and completion rates. 68 69 There are many barriers to exercise referral at an individual, social and system level.…”
Section: Providing Resourcesmentioning
confidence: 99%
“…Despite a rise in initiatives and research, 61 physical activity promotion in primary care remains inconsistent. [62][63][64][65][66][67] Exercise referral schemes have shown small positive effects on physical activity, 33 but with low attendance and completion rates. 68 69 There are many barriers to exercise referral at an individual, social and system level.…”
Section: Providing Resourcesmentioning
confidence: 99%
“…Because physical activity is a key contributor to CRF, including a PAS variable in an NEECRF model improves accuracy [ 3 , 8 , 16 ]. However, a recent review of distinct EHRs across 20 countries found that only 18.8% of family practice clinics had structured PAS questionaries embedded within the EHR, with documented PAS in the EHR ranging from 10% to 86% [ 15 ]. Notably, no validated questionaries designed for PAS-based NEECRF calculations were used.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the PAS model correlations are higher than our eCRF model without PAS; beyond genetics, PAS is an essential variable for modifying CRF [ 2 , 4 , 11 ]. Though these eCRF PAS-based correlations are higher, access to specific PAS data from existing EMR datasets is not likely to have been recorded in EMRs [ 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the type of variables used to calculate eCRF, a potentially rich data source may be found in electronic medical records (EMRs). However, EMRs do not typically have PAS information; therefore, it is impossible to conduct epidemiological studies using existing EMR data using PAS-based eCRF models [ 7 ]. However, EMRs do contain independent variables that have been used in previous eCRF PAS models (age, gender, BMI, resting heart rate, blood pressure, smoking) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%